Normative Analysis of Sheikh Bin Baz's Fatwa On Marriage With The Intention Of Divorce - Ahmad Raihan; Gusti Muzainah (Sharia Journal and Education Center Publishing, 2024)
Abstract Avoiding adultery is often a reason for people to hasten marriage. However, an interesting phenomenon that needs to be studied is